Comparison of Hematopoietic Stem Cell Transplantation Results in Patients with β-Thalassemia Major from Three Different Graft Types. (2nd January 2021) - Aydogdu, Selime; Toret, Ersin; Aksoy, Basak A.; Aydın, Muhammed Fatih; Cipe, Funda E.; Bozkurt, Ceyhun; Fisgin, Tunc
Abstract: Allogeneic hematopoietic stem cell transplantation (HSCT) is the curative therapy for β-thalassemias that induces severe life-threatening complications. The human leukocyte antigen (HLA) registries and umbilical cord blood banks have carried out diligent searches to find matched unrelated donors (MUDs) for about 70.0% of patients from 2000 onwards. The chance of finding a non-sibling fully matched family donors is higher in some ethnic groups in which consanguineous marriages are common. We have studied and compared transplant complications and outcomes in different graft types (sibling, non-sibling family and unrelated). The non-sibling matched family donor (MFD) group consisted of four mothers, three fathers, five cousins, one paternal uncle and one paternal aunt. There was no significant difference in the mean transfused CD34+ cells, engraftment, median days of neutrophil and platelet recovery were achieved ( p >  0.05). The distribution of postttransplant complication did not show any significant difference between groups ( p >  0.05). In univariate analysis and multivarite analyses, age, gender, Pesaro risk group (I-II vs. III) and ABO incompatibilty demonstrated a significant difference in disease free survival ( p  < 0.05). Furthermore, in the second step of investigating overall survival (OS), age, gender and Pesaro risk group (I-II vs. III) showed a significant difference ( p  < 0.05). There was no significant difference in transplant-related mortality (TRM) between groups. Non-sibling related donor transplants are important for populations where consanguineous marriages are common. Transplant groups according to graft type had similar thalassemia-free survival (TFS) and OS when using a treosulfan-based regimen in our study.